2017
DOI: 10.1155/2017/8612953
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Road Traffic Injuries among Different Road Users in the Gambia

Abstract: We identified risk factors for road traffic injuries among road users who received treatment at two major trauma hospitals in urban Gambia. The study includes pedestrians, bicyclists, motorcyclists, and drivers/passengers of cars and trucks. We examined distributions of injury by age, gender, collision vehicle types and vehicle category, and driver and environment factors. Two hundred and fifty-four patients were included in the study. Two-thirds were male and one-third female. Two-thirds (67%) of road traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
8
17
0
Order By: Relevance
“…This discrepancy may be explained by the fact that those RTA victims who were discharged home had minor injuries such as scratches or slight confusion. However, our findings are similar to those conducted in Ethiopia and Gambia which found low rates of hospital admission and deaths [11, 23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This discrepancy may be explained by the fact that those RTA victims who were discharged home had minor injuries such as scratches or slight confusion. However, our findings are similar to those conducted in Ethiopia and Gambia which found low rates of hospital admission and deaths [11, 23].…”
Section: Discussionsupporting
confidence: 90%
“…Road safety legislation, road infrastructure and affordable ways to maintain vehicles have not kept pace with the surge in vehicle numbers. Studies in Gambia, Burkina Faso and Tanzania have shown that many injuries occur at hot spots such as road intersections with or without traffic lights, during rush hours and at night [2325], and these factors may play a part in Guinea. Human behavior also plays an important role with speeding, careless driving and driving under the influence of alcohol being important factors contributing to RTA in many countries, and probably also in Guinea [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding our first objective, it is worth mentioning that the observed directionality of associations between human factors and infrastructure variables, resulted consistently with other studies previously performed with samples of cyclists [4,32] and diverse groups of road users, especially drivers with high exposure to diverse road risks [33,34]. Specifically, it is worth remarking on the associations reported between age of cyclists and road crash rates in the last 5 years which were in accordance with other empirical sources [35,36], i.e., cyclists with less age tend to accumulate higher crash rates (regardless of severity) when riding compared with those with a higher age/riding experience.…”
Section: Discussionsupporting
confidence: 87%
“…Human, environmental, road, and vehicle factors actively interact in RTI involvement [ 5 7 ]. Human factors, in which aberrant driving behaviors are central, profoundly contribute to RTIs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%